ON THE ISSUE OF LEGAL PROVISION OF FOOD SECURITY IN RUSSIA - T. Z. Yusupov (Russian Journal of Economics and Law)
The work views the issues of legal provision of food security in Russia. The state Doctrine of food security of the Russian Federation under the world financial and economic crisis is analyzed. The tools of legal regulation of agrarian-food economy sector and state agricultural insurance are described. The ways to improve the Russian agrarian legislation are studied. The principles, goals, main directions and measures for the state agrarian-food policy realization are summarized.